Differences Between Supplier Development Programme of Foreign and Local Malaysian Automotive Suppliers (Malaysian Management Journal, 2011)
Research into supplier development has raised issues on the buyer’s relationship with the supplier. A buyer with collaborative relationship would have more interest in supplier development. From the viewpoint of the suppliers, buyers who provided assistance could help the suppliers in developing their capability, a situation that might be particularly relevant in developing and emerging countries. The automotive manufacturers have implemented supplier development programmes for their suppliers, both in developed and developing countries. This raises a question on supplier development programmes in developing countries: How do supplier development programmes differ between a local (Malaysian) supplier and a foreign (non-Malaysian) supplier for Malaysian automakers (buyers)? In this research, interviews were conducted at three supplier organisations, of which one was Australian and two were Malaysian, where all three were suppliers for a Malaysian automaker. This study found that the Malaysian and Australian suppliers differed in supplier categories, customisation versus standardised products and buyer involvement. The study suggests that buyer differences with regard to supplier relationship, supplier commitment, type of product and size of supplier organisation play a role in supplier development.